ENVIRONMENTAL RECLAMATION AS STRATEGY FOR SUSTAINABILITY - Bressane, Adriano [UNESP]; Ribeiro, Admilson Irio [UNESP]; Medeiros, Gerson Araujo de [UNESP] (Escola Superior Dom Helder Camara, 2016)
The environmental change by the society is recurring and has been intensified since the first civilizations. However, the lack of conservationist practices has caused the emergence of degraded areas, whose recovery is fundamental for the sustainability. In this context, this paper aims at analyzing the environmental recovery as a public policy strategy supported in the Brazilian legislation. As methodology, a documental and analytical research was developed on the regulations, discussed at a multidisciplinary perspective, from the view of legal and engineering specialists, from the agricultural and environmental areas. As a result, it was identified a collection of rules pointing at a significant commitment on the definition of guidelines. On the other hand, this meaningful quantity of legal mechanisms, associated to misalignment, may cause damages to its effectiveness. In conclusion, we can consider that environmental reclamation is widely regulated, and it represents one of the main strategies of the environmental public policy adopted in Brazil. Nevertheless, it still requires advances to combine harmoniously practical and theoretical-conceptual aspects. Thus, considering the moment that Brazil is consolidating a new Forestry Code, we hope that the achieved outcomes can contribute to the debate and mobilization about the environmental reclamation as a strategy for sustainability.
Keywords: Degraded areas; Systemic perspective; Public policy